Outsourcing the Disbursement of Social Grants and Banking the Unbanked : the Case of Net1 UEPS Technologies, Ltd. in South Africa - Sharp, John (University of Pretoria, 2020)
Dissertation (MSocSci)--University of Pretoria, 2017.